Odpowiedzi

Najlepsza Odpowiedź!
2009-12-10T17:09:03+01:00
X-y=0
x+y+z=4
x+2y+3z=9

x=y
y+y+z=4
y+2y+3z=9

x=y
z=4-2y
3y+3(4-2y)=9

x=y
z=4-2y
3y+3(4-2y)=9

x=y
z=4-2y
3y+12-6y=9

x=y
z=4-2y
-3y=9-12

x=y
z=4-2y
-3y=-3

x=y
z=4-2y
y=1

x=1
z=4-2*1
y=1

x=1
z=2
y=1
------------------

3x-2y=5
2x-y=4

3x-2y=5
y=2x-4

3x-2(2x-4)=5
3x-2y=5

3x-4x+8=5
3x-2y=5

-x=-3 /*(-1)
3x-2y=5

x=3
3*3-2y=5

x=3
-2y=5-9

x=3
-2y=-4 /*(-1)

x=3
2y=4

x=3
y=2



2009-12-10T17:16:24+01:00
{3x-2y=5
{2x-y=4/*2

{3x-2y=5
{4x-2y=8

{-x=-3/(-1)
{3x-2y=5

{x=3
{9-2y=5

{x=3
{-2y=5-9

{x=3
{-2y=-4/:(-2)

{x=3
{y=2